Hepatology, Medicine and Policy - Lazarus, Jeffrey
Hepatology, Medicine and Policy considers articles on the prevention and management of viral and non-viral hepatitis and other liver disorders, including articles on the public health, policy and biomedical dimensions of these conditions.